Bridging communities, prevention, and heart health: U.S. strategies for CHW cardiovascular training and integration - Asare, Akua G.; Echols, Melvin R. (Frontiers in Epidemiology, 2025)
BackgroundIn the United States, cardiovascular disease (CVD) disproportionately affects communities facing adverse social determinants of health (SDOH). Community Health Workers (CHWs) can bridge gaps in trust, navigation, and culturally tailored education.MethodsWe conducted a U.S.–focused narrative review (2015–2025) of PubMed, Scopus, and Google Scholar, prioritizing empirical evaluations of CHW-led CVD interventions, training models, integration strategies, and financing mechanisms. International CHW programs were used only to extract practices transferable to U.S. delivery and payment contexts.ResultsMultidisciplinary team-based care demonstrates that engaging CHWs in US regions improves blood pressure control and medication adherence. Economic evaluations increasingly support CHW models for CVD prevention and control. Effective programs specify CHW task bundles (e.g., self-measured BP onboarding, adherence coaching, care navigation, SDOH linkage) and align training with national core competencies. Integration pathways include clinic-embedded, payer-based, public health, and community-based partnerships. U.S. reimbursement options are emerging through Medicare Community Health Integration/Principal Illness Navigation and state Medicaid mechanisms. Faith-based collaborations can extend reach when coupled with standardized training and simple outcome tracking.ConclusionsFor U.S. health systems and payers, immediate priorities are (1) competency-based CHW training with cardiac modules, (2) sustainable reimbursement tied to cardiovascular quality metrics, and (3) a minimal outcome set to demonstrate value. Global best practices should be adapted to the U.S. scope-of-practice, supervision, and documentation requirements to scale equitable CVD care.